Understanding and preparedness of manufacturing companies towards the proposed goods and service tax in Malaysia - Bidin, Zainol; Marimuthu, Munusamy (2015)
The Malaysian Government announced that the Goods and Services Tax (GST) would replace of Sales and Service Tax on 1 April 2015.The government would implement the GST system once everyone understands and familiar with the system.This study is aimed to discover the understanding and preparedness towards the implementation on the GST among managers in manufacturing companies in Malaysia.Two constructs namely understanding and preparedness were used to measure the GST perceptions.A survey was conducted by using mailed questionnaire to acquire the data from 2,600 managers of manufacturing companies throughout Malaysia.Only 173 responded where two questionnaires were found unusable giving almost 7% response rate.Data were analyzed using descriptive statistics.The reliability and validity tests were also performed on the two constructs.Overall, the results indicated that manufacturing companies in Malaysia have good understanding and well prepared towards the GST. All the items loading in the two constructs except one item (slightly less than 3.0) have mean score of above 3.00.The results of reliability for both constructs had shown the Cronbach alpha value above 0.70. Furthermore, the results of construct validity for both constructs also shown KMO values are more than 0.80. The results of the study provide invaluable inputs for the Government to implement GST to manufacturing companies in Malaysia.